PENGEMBANGAN LKPD BERBASIS PENDEKATAN KONTEKSTUAL PADA TEMA 1 PERTUMBUHAN DAN PERKEMBANGAN MAKHLUK HIDUP KELAS III SD - Irna Nopriani Tarigan,; Beta Rapita Silalahi, (Jurnal Cakrawala Ilmiah, 2024)
This research aims to develop LKPD based on a contextual approach (CTL) that is suitable for use in the learning process in fourth grade elementary school. This research is development research (Research and Development) using the ADDIE development procedure which consists of 5 stages. However, in this study the ADDIE procedure was used only up to stage 3, namely the development stage. The instrument used to collect data was a validation questionnaire. The validation questionnaire was given to several expert validators, namely teaching material expert validators, material expert validators and learning expert validators. The total score obtained from the final validation of the LKPD expert was 84.4, from the material expert validation, namely 100 and from the learning expert it was 97.4. The average score from the experts' assessments is 93.93. From these scores it can be said that the CTL-based LKPD developed is "Very Appropriate" for use in the learning process in class III elementary school